UMPSA helps early childhood educators master English - Noor Azlinda, Zainal Abidin; Ezihaslinda, Ngah; Noor Raha, Mohd Radzuan; Wan Jumani, Fauzi (UMPSA, 2024)
GAMBANG, 28 September 2024 – A total of 47 educators from various nurseries and kindergartens around Kuantan and Temerloh participated in the programme Little Learners, Big Future: Practical Instructional Approaches for Teaching English to Young Learners, organised by the Centre for Modern Languages (CML), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), at UMPSA Gambang Campus recently.